Парки-пам’ятки садово-паркового мистецтва у культурній спадщині: етимологія поняття, історія створення та художньо-естетичні особливості - Барановська, Надія; Baranovska, Nadiia (Видавництво Львівської політехніки, 2020)
У статті проаналізовано етимологію поняття “парку-пам’ятки садово-паркового мистецтва”, її статус і завдання, історію створення та характерні особливості цих об’єктів культурної спадщини, їхній взаємозв’язок із природою, роль і значення для збереження стильової та національно-культурної своєрідності. Увагу закцентовано на розкритті суспільно-культурної, мистецької та історичної цінності садово-паркових об’єктів з урахуванням їхнього художньо-естетичного свiту, планувальних і композиційних рішень, проблеми збереження та репрезентації в рамках чинного законодавства.

The article analyzes etymology of the concept “memorial park of landscape art”, its status and tasks, the history of creation and characteristic features of these objects of cultural heritage, their relationship with nature, role and importance for the preservation of national and cultural and style peculiarity. The attention is focused on the disclosure of the sociocultural, artistic and historical value of park and garden objects, taking into account their artistic and aesthetic world, planning and compositional solutions, problems of preservation and representation within the current legislation. Memorial parks of landscape art represent a significant part of the world, European and nationally-cultural heritage. They reflect the history of many cultures and nations, play an important role in the study of artistic culture, demonstrate the unity of man and nature, unification in a single composition of different types and styles of art. Important are their ecological and recreational functions, ability to meet aesthetic and recreational needs of people. The creators and founders of the historic memorial parks of landscape art were trying to creatively convey sociopolitical and economic changes in society, creatively reflect their requests for culture, new tastes, requests and opportunities. It was found, that memorial parks of landscape art have own long history and features that are determined by sociopolitical, artistically-aesthetic, natural, style, planning and compositional aspects and means of influence. They are a kind of original cultural embodiment of past historical epochs, which still retain the memory about their owners and historical events in different regions of Ukraine, testify about combination of tastes and cultures of different nations, and therefore are an invaluable achievement of the world and national cultural heritage. These are not only interesting landscapes and art objects, but also a specific illustration of philosophical views and their creative representation in the combination and interaction of man with nature. In addition, they have significant scientific, dendrological and recreational value, and therefore are subject of conservation and protection by the state.
Memorial parks of landscape art in the cultural heritage: etymology of the concept, history of creation and artistically-esthetic peculiarities
Keywords: парки-пам’ятки садово-паркового мистецтва; історія; культурна спадщина; художньо- естетичні особливості; садово-парковий ландшафт; композиція; memorial parks of landscape art; history; cultural heritage; artistic and aesthetic features; garden and park landscape; composition; 930.85; 712.253